2021
DOI: 10.22342/jme.12.1.12940.113-132
|View full text |Cite
|
Sign up to set email alerts
|

Digital Tools and Paper-and-Pencil in Solving-and-Expressing: How Technology Expands a Student’s Conceptual Model of a Covariation Problem

Abstract: This study aims at understanding the role of the tools chosen throughout the processes of solving a non-routine mathematical problem and communicating its solution. In assuming that problem-solving is a synchronous activity of mathematization and expression of mathematical thinking we take our proposed Mathematical Problem Solving with Technology (MPST) model to analyze the processes of solving-and-expressing-problems. Resorting to qualitative methods for data collection and analysis, we report on the case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
1
7
0
2
Order By: Relevance
“…The current study is largely in line with the research by Jacinto and Carreira (2021), showing that STEM tasks should be completed in the app and on paper to promote learning success. Solving problems in this fashion contributes to better understanding of the problem and a variety of ways to solve it, as well as activates students' thinking.…”
Section: Changes In the Assessment Of A Mobile App For Learning Stem ...supporting
confidence: 82%
See 1 more Smart Citation
“…The current study is largely in line with the research by Jacinto and Carreira (2021), showing that STEM tasks should be completed in the app and on paper to promote learning success. Solving problems in this fashion contributes to better understanding of the problem and a variety of ways to solve it, as well as activates students' thinking.…”
Section: Changes In the Assessment Of A Mobile App For Learning Stem ...supporting
confidence: 82%
“…Based on the results of teacher surveys, it can be concluded that educational applications provide numerous opportunities for learning, which is confirmed by the data obtained by Ahmed et al (2021), Jones et al (2013), Lindsay (2016), Olszewski and Crompton (2020). However, these apps should not completely replace the ability to actually complete tasks, as argued by Jacinto and Carreira (2021). The results of the conducted survey confirm that the so-called "forced" turn to distance learning should be in harmony with the traditional needs of students (e.g., live sintering, doing exercises by hand).…”
Section: Changes In the Assessment Of A Mobile App For Learning Stem ...mentioning
confidence: 60%
“…. x n 􏼈 􏼉 is a set composed of one character, (A, •) is a postexchangeable quasi group defined on A, and A + is a set composed of all nonempty character declarations in set A [31,32]. e character declaration transformations E and D. Based on the operation, ⊙ are defined as follows as equations ( 5) and ( 6):…”
Section: Implementation Of Hybrid Encryption Algorithm Based On the C...mentioning
confidence: 99%
“…We note that, although the processes are clearly defined, appear in a sequential list, and have seemingly distinct boundaries, in fact as admitted by the original models, in the MPST model they are rather flexible. For instance, while in studies with middle grade students the process communicate would emerge throughout the activity (Jacinto & Carreira, 2021), it is expected that it will not be patent in the activity of the participant in this study, due to the nature of the research setting (online observation of individual activity).…”
Section: Discussionmentioning
confidence: 99%
“…Actual mathematical problem-solving seldom occurs in a linear, straightforward way; instead, as shown with young or adult problem solvers, the process takes place in a cyclic way (Carlson & Bloom, 2005). This is also the case when problem solvers make use of digital tools in carrying out the process (Carreira & Jacinto, 2019;Jacinto & Carreira, 2021;Rott et al, 2021). However, the role of technology in triggering this cyclic activity and pushing the solver to move forward is still insufficiently understood.…”
Section: Introductionmentioning
confidence: 99%